Cyber security policy guidebook - Bayuk, Jennifer L. (John Wiley & Sons, 2012)
"Drawing upon a wealth of experience from academia, industry, and government service, this book details and dissects current organizational cybersecurity policy issues on a global scale. Using simple language, it includes a thorough description of each issue, lists pros and cons, documents policy alternatives for the sake of clarity with respect to policy alone, and dives into organizational implementation issues. It also equips the reader with descriptions of the impact of specific policy choices, both positive and negative. This book gives students, scholars, and technical decision-makers the necessary knowledge of cybersecurity policy in order to make more informed decisions"-- Provided by publisher.